2019
DOI: 10.3390/ijerph16214252
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Randomized Trial of Effects of Perioperative Oral Hygiene Instruction on Inpatients with Heart Diseases Using a Behavioral Six-Step Method

Abstract: The assessor-blinded, parallel-design, quasi-randomized study (alternating allocation) aimed to determine the effects of the six-step method on postoperative numbers of oral bacteria, periodontal status, and atrial fibrillation (AF) among inpatients with heart diseases and periodontitis. Seventy inpatients who received preoperative periodontal treatment were quasi-randomly assigned to intervention and control groups at University Hospital. The intervention group received intensive oral hygiene instruction usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(41 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…There were three SRs, one RCT, and five observational studies [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] . An SR by Wei et al [44] and Bardia et al [45] examined the incidence of postoperative pneumonia and nosocomial infections between patients who underwent oral rinsing with chlorhexidine and those who underwent rinsing with other drugs or no rinsing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were three SRs, one RCT, and five observational studies [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] . An SR by Wei et al [44] and Bardia et al [45] examined the incidence of postoperative pneumonia and nosocomial infections between patients who underwent oral rinsing with chlorhexidine and those who underwent rinsing with other drugs or no rinsing.…”
Section: Resultsmentioning
confidence: 99%
“…The RCT [47] examined the number of postoperative atrial fibrillation days between the intensive oral hygiene and routine oral hygiene groups and reported significantly fewer days in the intensive oral hygiene group (risk of bias; high). In the observational studies, Suzuki et al [51] reported significantly fewer days of postoperative fever-up in heart valve surgery patients who received periodontal therapy before surgery than in those who did not (risk of bias; moderate).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Omori et al [ 28 ] showed that in hospitalized patients with heart disease complicated with periodontitis, six-step oral hygiene enhancement can improve the occurrence of atrial fibrillation after cardiac surgery. All of the abovementioned studies [ 12 14 , 16 , 19 , 28 ] suggested that regular tooth brushing and oral care had an advantage in improving the occurrence and recurrence of atrial fibrillation. Therefore, the importance of long-term tooth brushing and oral hygiene should be emphasized in clinical practice and health promotion.…”
Section: Discussionmentioning
confidence: 99%
“…There is a demand for visiting home dental care, oral care for hospitalised patients, and oral health management for older people requiring long-term care. Previous studies have revealed that oral health management of dental hygienists for older adults or hospitalised patients is effective in improving not only oral health, but also general health conditions [ 2 , 3 , 4 ], thus, emphasizing the social role of dental hygienists as professionals in oral health management. However, the employment rate of dental hygienists in Japan is very low compared to other countries [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%